Pelaksanaan Layanan Konseling Individu dengan Teknik Cognitive Defusion dalam Menumbuhkan Rasa Percaya Diri pada Siswa Kelas X di MAN Lumajang - Haniyah, Rafidah; Noviyanti, Ade Irma; Sukmawati, Bhennita (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine the effectiveness of individual counseling services using the Cognitive Defusion technique in improving the self-confidence of tenth-grade students at MAN Lumajang. This technique, which is part of the Acceptance and Commitment Therapy (ACT) approach, helps individuals reduce the influence of negative thoughts by changing their perspective rather than eliminating the thoughts themselves. The background of this research lies in the low level of self-confidence among students, characterized by feelings of inferiority, self-doubt, fear of speaking in public, and withdrawal from social interactions. Such conditions hinder the learning process, social interaction, and personal development. This study employed a descriptive qualitative approach with two tenth-grade students identified as having low self-confidence based on initial observation and recommendations from school counselors. Data were collected through interviews, observations, and documentation, and validated through source triangulation. The results indicated that the application of Cognitive Defusion techniques in individual counseling enhanced students’ courage to speak, participate, and interact with peers. In conclusion, individual counseling using the Cognitive Defusion technique is effective in fostering students’ self-confidence.